Correlation Analysis between Residents’ Income Satisfaction and Mental Health Based on Big Data - Yile Wang; Hanbing Li; Brian Sheng-Xian Teo; Adam Amril Jaharadak (Occupational Therapy International)
This paper presents an in-depth study and analysis of the correlation between satisfaction with rural residents’ income and mental health well-being in the context of industrial structure upgrading. Most of the studies on residents’ subjective well-being from the perspective of relative income or income inequality have started from the happiness of rural residents and the satisfaction of rural residents’ life, and few scholars have focused on the psychological health of rural residents. Subjective well-being is significantly related to external and internal goals in desire. Life satisfaction is significantly and positively correlated with external and internal goals, as well as the six dimensions of desire, except for social identity; positive emotions are significantly and positively correlated with internal goals; negative emotions are only negatively correlated with self-acceptance, and there is a significant positive correlation between income level and desire. In vertical income, there is also a process of judging whether the expected income is achieved. If the expected income growth level is achieved, the income satisfaction will increase. Desire mediates the effect of income level on subjective well-being. Income level influences subjective well-being through internal goals; income level influences life satisfaction and positive emotions through external goals. The relationship between income inequality and mental health is influenced by the characteristics of the population, with women and middle-aged people being the most negatively affected. This relationship is also influenced by income level, with the effect of income inequality on mental health showing a negative effect in the lower and middle-income groups but a positive effect in the higher income groups. Income inequality affects residents’ mental health through the mediating effects of a sense of social justice, life stress, and trust in government. Inequality in household wealth can exacerbate the negative effects of income inequality on mental health.